2005
DOI: 10.1111/j.1469-7580.2005.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum positioning and partitioning in mitotic HeLa cells

Abstract: Cell division serves to distribute chromosomes and organelles into two daughter cells, but the mechanism of rough endoplasmic reticulum (RER) segregation in animal cell mitosis is poorly understood. Here we study the distribution of RER in mitotic HeLa cells and its relation to the cytoskeleton. At metaphase, the RER was located in the cell cortex and was most concentrated in two locations. Close to the plasma membrane the RER was closely associated with cortical actin, and after treatment with Latrunculin A R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 37 publications
3
40
1
Order By: Relevance
“…As observed previously, most of the ER is excluded from the spindle region (Jesch et al, 2001), whereas a fraction of the cisternal ER is located close to the spindle poles (WatermanStorer et al, 1993;Terasaki, 2000) (Figure 3). A characteristic layer of extended ER cisternae or sheets also follow the outline of the plasma membrane as detected previously by electron microscopy (McCullough and Lucocq, 2005). This packing of sheets is illustrated by the parallel distributions of GFP-Sec61␤ and the lipid dye FM4-64, which labels the plasma membrane, and by the distributions of GFP-Sec61␤ and cherry-actin, which labels the cortical actin layer immediately beneath the plasma membrane (Supplemental Figure 2C).…”
Section: The Mitotic Er Is Composed Primarily Of Extended Cisternaementioning
confidence: 78%
See 2 more Smart Citations
“…As observed previously, most of the ER is excluded from the spindle region (Jesch et al, 2001), whereas a fraction of the cisternal ER is located close to the spindle poles (WatermanStorer et al, 1993;Terasaki, 2000) (Figure 3). A characteristic layer of extended ER cisternae or sheets also follow the outline of the plasma membrane as detected previously by electron microscopy (McCullough and Lucocq, 2005). This packing of sheets is illustrated by the parallel distributions of GFP-Sec61␤ and the lipid dye FM4-64, which labels the plasma membrane, and by the distributions of GFP-Sec61␤ and cherry-actin, which labels the cortical actin layer immediately beneath the plasma membrane (Supplemental Figure 2C).…”
Section: The Mitotic Er Is Composed Primarily Of Extended Cisternaementioning
confidence: 78%
“…The extended ER pattern that is prominent throughout the cytosol of the mitotic cells is largely excluded from the central zone that contains the mitotic spindles and chromosomes of HeLa (Jesch et al, 2001;McCullough and Lucocq, 2005), BSC1 and CHO cells (Figure 2Bh and Supplemental Figure 1, B and D, respectively). In this region, the detectable ER show up as a limited number of tubules emanating from the spindle poles (e.g., a mean of 9 Ϯ 8 [mean Ϯ SD; n ϭ 13] tubules in HeLa cells, Figure 2Bc; also see Figure 3); these tubules represent ϳ0.1 Ϯ 0.2% (mean Ϯ SD; n ϭ 7) of the total ER GFP-Sec61␤ signal in the mitotic cell, as determined by their relative integrated fluorescence intensity.…”
Section: The Mitotic Er Is Composed Primarily Of Extended Cisternaementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the interphase peripheral ER is dispersed throughout the cytoplasm, whereas the mitotic ER is located near the PM and away from the mitotic spindle ( Fig. 2A) (McCullough and Lucocq 2005;Puhka et al 2007Puhka et al , 2012Anderson and Hetzer 2008b;Lu et al 2009;Hetzer 2010;Lu et al 2011;Smyth et al 2012). The mechanism and proteins involved in regulating ER movement during mitosis are not well understood; however, it was recently shown that phosphorylation of STIM1 is required to prevent the ER membrane from associating with the mitotic spindle (Smyth et al 2012).…”
Section: Er During Mitosismentioning
confidence: 99%
“…Analysis of ER structure in HeLa cells and CHO cells, by live 3D confocal fluorescence microscopy and electron microscopy (EM), reveals an interphase ER morphology that is cisternal in the perinuclear region and mostly tubular in the periphery towards the PM, and a mitotic morphology that is almost entirely cisternal (McCullough and Lucocq 2005;Lu et al 2009). In contrast, experiments where ER structure was analyzed by transmission EM and EM tomography of either chemically fixed or highpressure frozen cells, reveal an ER structure that is mostly cisternal in interphase and more fenestrated and tubular in mitosis (Puhka et al 2007(Puhka et al , 2012.…”
Section: Er During Mitosismentioning
confidence: 99%